Reorganize for resilience putting customers at the center of your business - Gulati, Ranjay (Harvard Business Press, 2009)
"In Reorganize for Resilience, strategy and organizational behavior expert Ranjay Gulati reveals how resilient companies prosper in both good times and bad - driving growth and increasing profitability by immersing themselves in the lives of their customers. Instead of pushing their own offerings on customers, these firms work from the outside in: identifying current and potential customer problems and then providing seamless, integrated products and services that address them." "Based on more than a decade of research in a variety of industries, this implementation focused guide shows how resilient companies break down internal barriers that impede action, build bridges across divisions, and create a network of collaborators. Using examples from companies including Cisco Systems, Lafarge, Starbucks, Best Buy, and Jones Lang LaSalle, Gulati describes the five key levers that together help create a resilient organization: coordination, cooperation, clout, capability, and connection."--BOOK JACKET.